Perceptions and Consumption Behavior of Middle-Income Communities Regarding the Increase in Gold Prices - Hafidz Aria Anggara; Dzikra Widia Setiawan; Sri Wahyuni N. Bahlawan; Diva Fadilah; Satria Yulianto; Jentot Tugiyono (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to explore middle-income households' perceptions of rising gold prices and examine how these perceptions influence consumption behavior and financial decision-making. Research Method: A qualitative descriptive approach was employed, using semi-structured, in-depth interviews with purposively selected participants with experience in gold ownership and household financial management. Secondary data, including economic reports, relevant literature, and gold price trends, were used to strengthen the contextual analysis. Data were analyzed inductively using the Miles and Huberman model. Results and Discussion: The findings indicate that many participants perceived gold as a safe haven asset capable of preserving wealth amid inflation and economic uncertainty. Rising gold prices encouraged adjustments in household consumption patterns, including reducing discretionary spending and reallocating resources toward gold investment through physical purchases, installment schemes, and digital platforms. However, participants demonstrated heterogeneous responses depending on their financial circumstances and risk perceptions. Gold ownership was generally associated with enhanced financial preparedness. Implications: The findings emphasize the importance of financial literacy and balanced household financial planning. Originality: This study integrates safe haven behavior, risk perception, and financial resilience to explain household responses to rising gold prices from a qualitative perspective.